A transgenic approach to identify thyroxine transporter-expressing structures in brain development - Lang, Ming-Fei; Salinin, S.; Ridder, D. A.; Kleesiek, J.; Hroudova, J.; Berger, S.; Schütz, G.; Schwaninger, Markus (Journal of neuroendocrinology, 2011)
Transporters are essential in thyroid hormone metabolism. Thyroxine (T4) is transported by solute carrier organic anion transporter 1c1 (SLCO1C1, OATP14) into the adult brain, where T4 is converted to 3,5,3′-triiodothyronine (T3). In adults, SLCO1C1 expression is found in two brain barrier structures: the blood-brain barrier (BBB) and choroid plexus. However, little is known about how T4 is transported in the developing brain, when the BBB is not yet completely formed. We employed bacterial artificial chromosome recombineering to generate transgenic mice carrying Cre recombinase in the Slco1c1 locus (Slco1c1-Cre mice). In Slco1c1-Cre mice Cre was expressed at the sites that have been previously reported for SLCO1C1 in adults. To trace Cre expression during development, we crossed Slco1c1-Cre transgenic mice with Rosa26 reporter mice. β-galactosidase staining showed Cre activity in neurones of various brain structures, such as cortical layer 2/3 and the hippocampus, suggesting transient Slco1c1 expression during brain development. At embryonic day15, SLCO1C1 was expressed at the same site as TBR2, a marker of neuronal progenitors. Neurones that express SLCO1C1 during their development could be T4 sensitive. In support of this hypothesis, hypothyroxinaemia induced by propylthiouracil treatment of dams decreased the number of β-galactosidase-positive neurones in cortical layer 2/3 of newborn Slco1c1-Cre/Rosa26 mice. In conclusion, by generating Slco1c1-Cre transgenic mice, we demonstrated that SLCO1C1 is expressed in the neuronal cell lineage during brain development. Expression of SLCO1C1 may underlie the extraordinary sensitivity of specific neuronal populations to hypothyroxinaemia.